Amorphous Fe‐Based Nanoagents for Self‐Enhanced Chemodynamic Therapy by Re‐Establishing Tumor Acidosis. (29th November 2019) - Chen, Xiaoyan; Zhang, Huilin; Zhang, Meng; Zhao, Peiran; Song, Ruixue; Gong, Teng; Liu, Yanyan; He, Xinhong; Zhao, Kuaile; Bu, Wenbo
Abstract: Chemodynamic therapy (CDT) by introducing the Fenton‐/Fenton‐like reaction in an acidic and H2 O2 environment for toxic hydroxyl radical (OH) generation, is a newly developed tumor‐selective therapeutic. However, tumor acidosis, characterized by extracellular acidity (pHe ≈ 6.5) and intracellular alkalinity (pHi ≈ 7.2), undoubtedly confers a large chemical barrier for effective implementation of intracellular CDT and thus limits its functional activity and therapeutic efficacy. Here, the unique amorphous iron nanoparticles (AFeNPs) loaded with carbonic anhydrase IX inhibitor (CAI) are constructed to re‐establish tumor acidosis with decreased pHi and increased pHe via inhibiting the over‐expressed CA IX in cancer cells by CAI for self‐enhanced CDT. The suppression of CA IX leads to H + accumulation in cells that could accelerate the AFeNPs‐based Fenton reaction to drastically exacerbate oxidative stress in cells and subsequently induce cell death; meanwhile, the inhibition of H + formation outside cells efficiently represses the potential of tumor invasion and metastasis owing to the insufficient acidic ions for degradation of tumor extracellular matrix. Re‐established tumor acidosis not only assists in the optimization of CDT, but also presents an opportunity for the development of new antitumor methods that are more tumor‐acidity specific. Abstract : Amorphous Fe 0 nanoparticles loaded with a carbonic anhydrase IX inhibitor (CAI) are constructed to inhibit the over‐expressed CA IX in cancer cells for re‐established tumor acidosis, with increased acidification in cells for enhanced chemodynamic therapy, and decreased formation of acidic ions outside for effective inhibition of tumor invasion and metastasis.